Pedagogical Content Knowledge: How do Pre-service Teachers Adapt and Employ it in their Teaching? - Abd Rahman, Fadzilah; Scaife, Jon (2008)
Pedagogical content knowledge (PCK) is increasingly recognized as an essential component in assessing pre-qualified teachers and in establishing ‘quality teaching’. PCK refers to an understanding of subject matter; an understanding of students: their abilities and interests and how they respond to diverse situations; an application of different teaching strategies; and how various types of classroom activity might be managed. Although PCK has come to be seen as important, details of its development, depth and quality among pre service teachers (PSTs) has remained something of mystery, as has the capability of PSTs to adapt and employ PCK in their actual teaching. As an effort to develop a coherent understanding of prospective teachers’ construction and application of PCK, this study is a reflection on two questions. First, to what extent are PSTs prepared in terms of PCK at the end of their teacher education programme and secondly, how do PSTs apply their PCK during their teaching practices? The paper illustrates the results of a study that involved a sample of 74 student teachers at a university in Malaysia. At the beginning of the study, each student teacher was given a questionnaire. Based on an analysis of the completed questionnaires, 11 of the pre service teachers were observed. Result indicate that, while their self-rating scores were good, they were still a little below the average in practices.